On Evolution and the Quantum and Classical Regimes in Brain Function. - Gupta, Priti; Markan, C. M. (Journal of Consciousness Studies)
As species evolved, consciousness (awareness) manifested at different levels: physical, mental, and subtle. But why different species exhibit different grades of consciousness continues to intrigue researchers. A plausible reason could be that adaptation to environmental changes, and hence survival and evolution, all depend on the level of consciousness species possess. This could be the reason why evolutionarily older species (with lower order consciousness) only implicitly (slowly and unconsciously) adapt, whereas evolved species (with higher order consciousness) explicitly (quickly and consciously) adapt to unforeseen situations gaining tremendous survival advantage. This ability requires exploring innumerable possibilities including representations that may not have been experienced before and requires faster, brain-wide computations. We argue that the transition from slow adaptation to fast learning can be explained by considering two different regimes of computation in the brain: a Classical Resime based on slow neuronal signalling, and a much faster Quantum Resime marked by subtler quantum computations at the sub-neuronal level. We conjecture that as brains of species increased in size, a threshold was reached, beyond which species could volitionally control attention and exploit the Quantum Regime which not only enabled them to quickly perform non-local computations, develop dynamic brain-wide neural associations, and adapt very fast, but also be mentally aware, observe themselves, and hence speed-up their own evolution.